Retracted: Study of Suregada Multiflora Leaves Extract as a Green Corrosion Inhibitor on Iron in HCl Medium - Pokhrel, Dilliram; Chatterjee, Abhik (Damak Campus Journal, 2023)
Retraction: On 29th July 2024 this article was retracted because it had already been published in another journal.